The Evolution of Circular Economy Research Based on Bibliometric Analysis of International Publications 2010–2024 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
The circular economy has emerged as a key concept in addressing global sustainability challenges, particularly those related to resource depletion, waste generation, and environmental degradation. This study aims to analyze the evolution of circular economy research based on international publications indexed in the Scopus database from 2010 to 2024. A bibliometric approach was employed to examine publication trends, collaboration networks, and thematic structures within the literature. Data were analyzed using VOSviewer to generate visualizations of co-authorship networks, keyword co-occurrence, and research density. The results indicate a significant increase in circular economy research over the past decade, reflecting growing academic and policy interest in sustainable production and consumption systems. Co-authorship analysis reveals the presence of several collaborative research clusters connected by influential authors who facilitate knowledge exchange across institutions and regions. Keyword co-occurrence analysis shows that circular economy research is strongly associated with themes such as sustainability, waste management, recycling, and life cycle analysis. In addition, technological topics including wastewater treatment, biomass utilization, and plastic recycling appear as important subthemes supporting circular resource flows. Density visualization further indicates that circular economy and sustainability remain the most dominant concepts within the field. Overall, the findings demonstrate that circular economy research has developed into an interdisciplinary domain integrating environmental science, industrial systems, and sustainability studies. This study provides a comprehensive overview of the intellectual structure of circular economy research and offers insights into emerging research directions for future studies.